- #1
MarkFL
Gold Member
MHB
- 13,288
- 12
Recently I was sent an ODE with the instructions to solve using the annihilator method which I have not used in over 15 years. This is my working, and I was hoping for feedback to see if I have correctly and efficiently applied the method.
Here is my working:
We are given the ODE:
(1) $\displaystyle y''+3y'-10y=xe^x+x+1$
Since $\displaystyle (D-1)^2$ annihilates $\displaystyle xe^x$ and $\displaystyle D^2$ annihilates $\displaystyle x+1$ then:
$\displaystyle A\equiv (D(D-1))^2$
annihilates $\displaystyle xe^x+x+1$.
Therefore, applying $\displaystyle A$ to both sides of (1) yields:
$\displaystyle A[y''+3y'-10y]=A[xe^x+x+1]$
$\displaystyle (D(D-1))^2(D^2+3D-10)[y]=0$
(2) $\displaystyle (D(D-1))^2(D+5)(D-2)[y]=0$
The auxiliary equation associated with (2) is:
$\displaystyle r^2(r-1)^2(r+5)(r-2)=0$
which has the roots:
$\displaystyle r=-5,\,0,\,1,\,2$ where the roots $\displaystyle r=0,\,1$ are repeated roots, i.e., of multiplicity 2.
Hence, a general solution to (2) is:
(3) $\displaystyle y(x)=c_1+c_2x+c_3e^x+c_4xe^x+c_5e^{2x}+c_6e^{-5x}$
Now, recall that a general solution to (1) is of the form $\displaystyle y(x)=y_h(x)+y_p(x)$. Since every solution to (1) is also a solution to (2), then $\displaystyle y(x)$ must have the form displayed on the right-hand side of (3). But, we recognize that:
$\displaystyle y_h(x)=c_5e^{2x}+c_6e^{-5x}$
and so there must exist a particular solution of the form:
$\displaystyle y_p(x)=c_1+c_2x+c_3e^x+c_4xe^x$
In order to substitute this into (1), we must first compute:
$\displaystyle y_p'(x)=c_2+c_3e^x+c_4e^x(x+1)$
$\displaystyle y_p''(x)=c_3e^x+c_4e^x(x+2)$
and so we find:
$\displaystyle (c_3e^x+c_4e^x(x+2))+3(c_2+c_3e^x+c_4e^x(x+1))-10(c_1+c_2x+c_3e^x+c_4xe^x)=xe^x+x+1$
Collecting like terms, we may write:
$\displaystyle (-6c_4)xe^x+(5c_4-6c_3)e^x+(-10c_2)x+(3c_2-10c_1)=(1)xe^x+(0)e^x+(1)x+(1)$
Equating coefficients yields:
$\displaystyle -6c_4=1\,\therefore\,c_4=-\frac{1}{6}$
$\displaystyle 5c_4-7c_3=0\,\therefore\,c_3=-\frac{5}{36}$
$\displaystyle -10c_2=1\,\therefore\,c_2=-\frac{1}{10}$
$\displaystyle 3c_2-10c_1=1\,\therefore\,c_1=-\frac{13}{100}$
Thus, we have:
$\displaystyle y_p(x)=-\frac{13}{100}-\frac{1}{10}x-\frac{5}{36}e^x-\frac{1}{6}xe^x$
and so, the general solution to (1) is:
$\displaystyle y(x)=c_1e^{2x}+c_2e^{-5x}-\frac{13}{100}-\frac{1}{10}x-\frac{5}{36}e^x-\frac{1}{6}xe^x$
Here is my working:
We are given the ODE:
(1) $\displaystyle y''+3y'-10y=xe^x+x+1$
Since $\displaystyle (D-1)^2$ annihilates $\displaystyle xe^x$ and $\displaystyle D^2$ annihilates $\displaystyle x+1$ then:
$\displaystyle A\equiv (D(D-1))^2$
annihilates $\displaystyle xe^x+x+1$.
Therefore, applying $\displaystyle A$ to both sides of (1) yields:
$\displaystyle A[y''+3y'-10y]=A[xe^x+x+1]$
$\displaystyle (D(D-1))^2(D^2+3D-10)[y]=0$
(2) $\displaystyle (D(D-1))^2(D+5)(D-2)[y]=0$
The auxiliary equation associated with (2) is:
$\displaystyle r^2(r-1)^2(r+5)(r-2)=0$
which has the roots:
$\displaystyle r=-5,\,0,\,1,\,2$ where the roots $\displaystyle r=0,\,1$ are repeated roots, i.e., of multiplicity 2.
Hence, a general solution to (2) is:
(3) $\displaystyle y(x)=c_1+c_2x+c_3e^x+c_4xe^x+c_5e^{2x}+c_6e^{-5x}$
Now, recall that a general solution to (1) is of the form $\displaystyle y(x)=y_h(x)+y_p(x)$. Since every solution to (1) is also a solution to (2), then $\displaystyle y(x)$ must have the form displayed on the right-hand side of (3). But, we recognize that:
$\displaystyle y_h(x)=c_5e^{2x}+c_6e^{-5x}$
and so there must exist a particular solution of the form:
$\displaystyle y_p(x)=c_1+c_2x+c_3e^x+c_4xe^x$
In order to substitute this into (1), we must first compute:
$\displaystyle y_p'(x)=c_2+c_3e^x+c_4e^x(x+1)$
$\displaystyle y_p''(x)=c_3e^x+c_4e^x(x+2)$
and so we find:
$\displaystyle (c_3e^x+c_4e^x(x+2))+3(c_2+c_3e^x+c_4e^x(x+1))-10(c_1+c_2x+c_3e^x+c_4xe^x)=xe^x+x+1$
Collecting like terms, we may write:
$\displaystyle (-6c_4)xe^x+(5c_4-6c_3)e^x+(-10c_2)x+(3c_2-10c_1)=(1)xe^x+(0)e^x+(1)x+(1)$
Equating coefficients yields:
$\displaystyle -6c_4=1\,\therefore\,c_4=-\frac{1}{6}$
$\displaystyle 5c_4-7c_3=0\,\therefore\,c_3=-\frac{5}{36}$
$\displaystyle -10c_2=1\,\therefore\,c_2=-\frac{1}{10}$
$\displaystyle 3c_2-10c_1=1\,\therefore\,c_1=-\frac{13}{100}$
Thus, we have:
$\displaystyle y_p(x)=-\frac{13}{100}-\frac{1}{10}x-\frac{5}{36}e^x-\frac{1}{6}xe^x$
and so, the general solution to (1) is:
$\displaystyle y(x)=c_1e^{2x}+c_2e^{-5x}-\frac{13}{100}-\frac{1}{10}x-\frac{5}{36}e^x-\frac{1}{6}xe^x$